The Criminological Ideas in the Criminal Enforcement of Illegal Logging - Dodyx Bremiardika; Rakhmat Bowo Suharto; R. Sugiharto Sugiharto (Law Development Journal, 2022)
The purpose of this paper is to examine and analyze the Criminology review of the factors that cause the occurrence of illegal logging crimes. In this paper, the author uses a normative juridical method. In the conclusion of the discussion that the factors of the occurrence of illegal logging in the perspective of criminology, namely first, the legal factor itself, the better a legal regulation, the more likely it is to enforce it. Both factors are law enforcement, law enforcement is strongly influenced by law enforcement officials. If a regulation is good but the quality and quantity of law enforcement apparatus is low, then the desired law will not be realized. Third, cultural factors play an important role in the occurrence of illegal logging. Illegal logging perpetrators commit these crimes because there are cultural demands that require them. Indonesia has hundreds of tribes and cultures in which the interior is very diverse. Fourth, Community factors can also affect law enforcement itself, because law enforcement comes from the community and aims to achieve peace in society. In this case what is important is the legal awareness of the community, the higher the legal awareness of the community, the better law enforcement.